Radical Historicism and Philosophical Reflection of Cultural Crises - Donskis, Leonidas (Problemos, 1991)
The problem of the crises of culture is a matter of great importance and one of the most urgent problems in philosophy of history and theory of culture. The article deals with the problem in the context of the problem of historicism. The methodological significance of the analysis of evolutionism and cyclical theory is especially emphasized. This article is also an attempt to summarize theoretical preconditions of the rise and sources of radical historicism, and by the way to show the connection between radical historicism and the problem of cultural crises.